Osteoarticular involvement in childhood brucellosis: experience with 133 cases in an endemic region - Bosilkovski, Mile; Kirova-Urosevic, Valerija; Cekovska, Zaklina; Labacevski, Nikola; Cvetanovska, Marija; Rangelov, Goran; Cana, Fadilj; Bogoeva-Tasevska, Suncica (Wolters Kluwer/Lippincott, 2013)
Aim: To describe the main clinical and laboratory characteristics, frequency and distribution of osteoarticular involvement, therapeutic options and outcome in children with osteoarticular brucellosis. Methods: This descriptive study includes 133 pediatric patients with osteoarticular brucellosis who were treated at the University Clinic for Infectious Diseases and Febrile Conditions in Skopje, Republic of Macedonia, during the period between 1989 and 2011. Brucellosis was presumptively diagnosed on the basis of clinical signs and confirmed by the detection of specific antibodies at significant titers. Results: The median age of patients was 9 years (range, 2-14 years) and 63.9% were males. Family history of brucellosis was present in 54.1%. The dominant clinical symptoms were arthralgia and fever in 77.4% and 73.7%, respectively, and the dominant sign was hepatomegaly in 73.7% of patients. The main laboratory abnormalities were elevated C-reactive protein (81.0%) and circulating immunocomplexes (80.7%). In 71.4% of patients, the osteoarticular involvement was monoarticular. Hip arthritis was present in 49.6%, followed by the knee in 30.1%. Various therapeutic regimens with a duration of 6 weeks were used. In 87 patients during a follow-up of at least 6 months, relapse occurred in 13.8%. Conclusions: Osteoarticular involvement is frequent in children with brucellosis. It is most often manifested with monoarthritis of the large weight-bearing joints. Brucellosis should be included in the differential diagnosis of childhood arthritis in endemic countries, especially in the presence of family history, contact with infected animals or ingestion of unpasteurized food products, fever and hepatomegaly.